Quality of life and nursing care for women in the climacteric period: a literature review (Research, Society and Development, 2020)
The climacteric is a biological process experienced by women that corresponds to the transition from the reproductive cycle to the non-reproductive cycle, occurring commonly between 45 and 65 years of age, and has as its main landmark menopause, designated as the last menstrual cycle. This study aims to investigate the main changes in climacteric in women's health, its implications for the quality of life of climacteric women and the main nursing behaviors in health care for women in the climacteric period. Narrative literature review study carried out by searching for articles in the Virtual Health Library, in March 2020. The study sample consisted of 6 studies published in the last 5 years. The results revealed that the signs and symptoms experienced by women in menopause are diverse, but that the psychological components have more impact on quality of life than physical symptoms. In addition, nursing care for climacteric women is geared towards health education, although there are gaps and limitations of health professionals regarding the approach to this topic, requiring the continuing education of health professionals for comprehensive quality care.